Rational design of novel nanostructured arrays based on porous AAO templates for electrochemical energy storage and conversion. (January 2019) - Wei, Qiliang; Fu, Yanqing; Zhang, Gaixia; Yang, Dachi; Meng, Guowen; Sun, Shuhui
Abstract: Nanostructured materials have attracted much attention in electrochemical energy storage and conversion (EESC) technologies such as batteries, fuel cells and supercapacitors. In particular, ordered arrays of one-dimensional (1D) nanorods/nanowires, and nanotubes, two-dimensional (2D) nano-thin sheets and three-dimensional (3D) nano-architectures, etc. have aroused great interest due to their unique intrinsic properties and much improved performances in EESC. Among various synthetic routes for these ordered nanostructures, ordered nanoporous anodic aluminum oxide (AAO) template assisted method has drawn particular attention because of AAO template's outstanding chemical and thermal stability, easy fabrication process, hardness, cost-effective, versatility and high surface area. This review begins with the introduction on the basic structures and properties of the porous AAO templates, and then mainly summarizes recent progress in the AAO-template directed growth of various 1D, 2D and 3D ordered nanostructure arrays for applications in typical EESC systems, including lithium-ion batteries (LIBs), lithium-sulfur (Li-S) batteries, lithium-oxygen (Li-O2 ) batteries, supercapacitors and fuel cells, followed by outlook for future research. Graphical abstract: fx1 Highlights: The basic structure and typical synthesis process of AAO templates are introduced. The synthesis of 1D, 2D and 3D nanoscale materials based on AAO template are summarized. The applications of nanostructures based on AAO in batteries, supercapacitors and fuel cells are reviewed. Future possible prospects based on AAO template are proposed.